Little Red Riding Hood: The other side of the story. Issue 2 (1st December 2014) - Ayiter, Elif; Dahlsveen, Heidi
This article wishes to present three virtual art ecologies that were created in 2013 in the metaverse of Second Life, involving a reinterpretation of the folk tale Little Red Riding Hood (LRRH). The tale of LRRH has many layers of complexity that are open to many varied interpretations, some of which were tackled by the participating artists and will be discussed in this text. Beyond presenting the work itself, this article also wishes to discuss a theoretical framework regarding storytelling, especially as it relates to today's information society and its offshoots, online virtual worlds.